Factors that influencing inflation rate in Malaysia / Siti Hafizah Akbar - Akbar, Siti Hafizah (2015)
The aim of this study is to investigate the relationship between inflation rate and gross domestic production, unemployment rate, exchange rate, interest rate and fiscal deficit. The study used four models of Multiple Linear Regression in order to find the relationship between inflation rate and gross domestic production, unemployment rate, exchange rate, interest rate and fiscal deficit. The quarterly data was collected from 1996 until 2014. From the result, it reveals that gross domestic production and interest rate have positive significant relationship toward inflation rate while unemployment rate has positive insignificant relationship toward inflation rate. Exchange rate and fiscal deficit have negative insignificant relationship toward inflation rate. It means that there are effect between inflation rate and gross domestic production and interest rate. These results further our understanding of the relationship between inflation rate and gross domestic production, unemployment rate, exchange rate, interest rate and fiscal deficit and should be useful for public, industries and policy makers.